Intrinsic organization of the corpus callosum - Barbaresi, Paolo; Fabri, Mara; Lorenzi, Teresa; Sagrati, Andrea; Morroni, Manrico (Frontiers in Physiology, 2024)
The corpus callosum - the largest commissural fiber system connecting the two hemispheres – is considered essential for bilateral sensory integration and higher cognitive functions. Most studies exploring the corpus callosum have examined either the anatomical, physiological and neurochemical organization of callosal projections or the functional and/or behavioral aspects of the callosal connections after complete/partial callosotomy or callosal lesion. There are no works addressing the intrinsic organization of the corpus callosum. We review the existing information on the activities that take place in the commissure in three sections: I) topographical and neurochemical organization of intracallosal fibers; II) role of glia in the corpus callosum; and III) role of intracallosal neurons.